2013
DOI: 10.1111/cdev.12052
|View full text |Cite
|
Sign up to set email alerts
|

Increases in Cognitive and Linguistic Processing Primarily Account for Increases in Speaking Rate With Age

Abstract: Age-related increases of speaking rate are not fully understood, but have been attributed to gains in biologic factors and learned skills that support speech production. This study investigated developmental changes in speaking rate and articulatory kinematics of participants aged 4 (N = 7), 7 (N = 10), 10 (N = 9), 13 (N = 7), 16 (N = 9) years and young adults (N = 11) in speaking tasks varying in task demands. Speaking rate increased with age, with decreases in pauses and articulator displacements but not inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 50 publications
(67 reference statements)
2
69
1
5
Order By: Relevance
“…Yet, after ensuring that their findings cannot be attributed to differences in utterance length, these studies failed to provide an explanation for this result. In contrast, the majority of studies performed on English speakers has shown that men and women use similar speaking rate [21,32,39].…”
Section: Speaking Rate and Gendermentioning
confidence: 90%
See 2 more Smart Citations
“…Yet, after ensuring that their findings cannot be attributed to differences in utterance length, these studies failed to provide an explanation for this result. In contrast, the majority of studies performed on English speakers has shown that men and women use similar speaking rate [21,32,39].…”
Section: Speaking Rate and Gendermentioning
confidence: 90%
“…It has also been suggested that children increase their speaking rate with age, due to a gradual cognitive and linguistic development, which facilitates more fluent speech by reducing disfluency. This, in turn, leads to the observed overall increase in speaking rate [32].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…From preschool years onward, speakers predictably change articulatory strategies, such as increasing or decreasing oral opening, for different tasks. Speaking tasks that require greater hyper-articulation so that content is conveyed to a listener, such as narrative retells, are produced with faster movement speeds and slower speaking rates because oral excursions are increased [29]. In contrast, tasks with increased articulatory demands and little linguistic content (e.g., diadochokinetic task, such as saying “ba” quickly and repeatedly) are produced with hypo-articulation or smaller oral excursions, resulting in slower movement speeds but faster speaking rates [29].…”
Section: Task Demandsmentioning
confidence: 99%
“…These reference markers were used to subtract head movement from the movement traces of the jaw markers and used to establish an anatomic coordinate system as well as reduce motion artifacts during post-processing of the kinematic data [22, 23]. …”
Section: Methodsmentioning
confidence: 99%